Perceptions of hospital manual handling policy and impact on nursing team involvement in promoting patients' mobility. Issue 1 (4th August 2014) - Kneafsey, Rosie; Clifford, Collette; Greenfield, Sheila
<x xml:space="preserve">Abstract</x> Aims and objectives To report the findings gained from interviews with hospital nurses and care assistants, regarding the impact of hospital manual handling policies on their role in maintaining and promoting patients' mobility. Background Older hospitalised adults often experience deteriorations in mobility, which are often partially caused by protective or custodial care practice and environments that promote patient dependency. Hospital‐induced mobility loss may be conceptualised as a problematic source of iatrogenic patient harm, worthy of attention from a patient safety standpoint. Preventative rehabilitation nursing interventions have the potential to prevent mobility loss. Design Grounded theory study. Methods Data were collected in three clinical settings: general rehabilitation, spinal injuries and stroke rehabilitation. Semi‐structured interviews with 39 rehabilitation staff were completed. Results Perceptions of hospital manual handling policy were described via four subcategories: policy as stimulus to improved practice; policy as divorced from reality; policy as threat; and policy as hindrance to rehabilitation. Conclusions Hospital manual handling policy was perceived negatively by some nursing team members both as a threat and as a barrier to patients' rehabilitation. Risk aversion, divided teamwork practices and overuse of patient handling equipment were matters of concern. Relevance to clinical practice Perceptions of hospital manual handling policy should be openly discussed by nursing managers and direct care providers. It is important to recognise that beliefs about and perceptions of policy will often impact later on staff practices and behaviours. Unintended consequences arising from dominant interpretations of manual handling policy must be acknowledged and risks identified. It is important that practitioners balance risk assessment and prevention of falls with patients' needs for mobilisation.